Clinical significance in non-cystic fibrosis bronchiectasis followed in a real practice - Newton Santos de Faria Júnior; Amilcar Marcelo Bigatão; Sérgio Ricardo Santos; Fernando Sérgio Studart Leitão Filho; José Roberto Jardim; Luis Vicente Franco Oliveira
INTRODUCTION: Bronchiectasis is a chronic disorder characterized by permanent dilation of the bronchi and bronchioles accompanied by inflammatory changes in the walls of these structures and adjacent lung parenchyma. OBJECTIVE: The aim of the present study was to perform a clinical and functional characterization of adult patients with non-cystic fibrosis bronchiectasis. METHODS: A clinical, descriptive, retrospective, case-series study was carried out involving 232 patients with non-cystic fibrosis bronchiectasis treated at a lung ambulatory between 2004 and 2012. RESULTS: The sample consisted of 232 patients (134 females; mean age: 52.9 years ± 17.7; body mass index: 23.5 kg/m² ± 4.4). The predominant symptoms were cough (91.4%), expectoration (85.8%) and dyspnea (76.3%). The majority of cases were of a non-tuberculosis etiology (64.7%). Regarding lung function, the obstructive breathing pattern was predominant (43.5%). The most common comorbidities were of a cardiovascular origin (51.0%). CONCLUSIONS: Adult patients with non-cystic fibrosis bronchiectasis (mainly post-infection or post-tuberculosis in origin) are characterized by a low educational level, excessive cough, sputum, dyspnea, muscle fatigue, an obstructive breathing pattern with frequent hypoxemia and multiple comorbidities, mainly of a cardiovascular origin. However, our patients have a low index of exacerbations and hospitalizations that can be assigned to a clinical protocol for monitoring.